Vector spatial and spatiotemporal laser solitons - Fedorov Sergey V.; Veretenov Nikolay A.; Rosanov Nikolay N. (Nanophotonics)
Dissipative optical solitons, i.e. packets of radiation localized not due to the presence of optical inhomogeneities of the scheme or medium, but due to the balance of energy inflow and outflow in a nonlinear medium, deserve special attention for a number of reasons. First, these solitons are “calibrated” with a discrete set of basic parameters. This will lead to their increased stability: dissipative solitons are attractors, they are not sensitive to small perturbations. Second, progress in laser technology and the emergence of new laser and nonlinear optical materials provides an opportunity not only to study the rich physics of dissipative solitons, but also to propose their promising applications. This paper, which combines both a review of the current level of theory and original results, is devoted mainly to new types of these solitons. These types exploit the topological features of structured radiation, characteristic of vector, polarization dissipative solitons, which have a nontrivial internal structure. We sequentially present one-dimensional (1D), two-dimensional (2D) and three-dimensional (3D) polarization solitons, identify limitations in the topological protection of the information that can be encoded by topological charges and indices and discuss development prospects in this area.